2008
DOI: 10.1002/app.29146
|View full text |Cite
|
Sign up to set email alerts
|

Effect of die design on die drool phenomenon for metallocene based LLDPE: Theoretical and experimental investigation

Abstract: The effect of die design on the die drool phenomenon was investigated for metallocene based LLDPE. It has been found that die exit opening and the flared die design can significantly reduce the die drool phenomenon. Moreover, theoretical research has revealed that die drool onset can be explained by the negative/nonmonotonic pressure profile generated inside the die and/or at the die exit region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…As shown in [4][5][6][7][8][9], formation of die drool phenomenon is influenced by several factors like low molecular fractions of the polymer and its structure, volatiles, die swell, die design etc. However, serious research about the die drool phenomenon for HDPE polymers has not been performed yet.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in [4][5][6][7][8][9], formation of die drool phenomenon is influenced by several factors like low molecular fractions of the polymer and its structure, volatiles, die swell, die design etc. However, serious research about the die drool phenomenon for HDPE polymers has not been performed yet.…”
Section: Introductionmentioning
confidence: 99%
“…Chaloupková and Zatloukal [13] in 2009 mathematically modelled polymer melt flow in die outlet zone and they disclosed area of negative pressure near the die exit edge contributing to material separation from the matrix. Further, they concluded that negative pressure is crucial important variable for die drool phenomenon.…”
Section: Breakthrough Work Focused On Die Drool Phenomenonmentioning
confidence: 99%
“…This reduction author attributes to a decrease in the work of adhesion which is related to the surface energies of the die-wall material and the polymer melt. Another contribution contains chamfer of the die exit edge [13]. Surprisingly, if the chamfered die exit edge angle is 45° accumulated drool mass is then dramatically reduced.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…can be found in open literature [4][5][6][7][8][9][10]. Further, three recently published works are focused on die drool phenomenon during HDPE extrusion.…”
Section: Introductionmentioning
confidence: 99%